Impact of Physical Activity and Exercise Modalities on Individual Components of Metabolic Syndrome: A Narrative Review - Pastuszak, Andżelika; Czechowicz, Katarzyna; Błaszczak, Maciej; Leja, Wiktoria; Lech, Jakub; Zulfiqar, Zeeshan; Kot, Jakub; Szczupaj, Maciej; Borkowski, Konrad; Rudnicki, Jakub (Quality in Sport, 2026)
Background: Metabolic syndrome (MetS) is an increasingly prevalent global health condition that increases the risk of developing type 2 diabetes mellitus and cardiovascular disease. Regular physical activity is recognized as one of the most important modifiable factors in both prevention and management of MetS. Aim: This narrative review evaluated the effect of physical activity on each of the major elements of metabolic syndrome. Material and methods: A narrative review was conducted using a structured search of the PubMed/MEDLINE database. The following keywords were applied: “metabolic syndrome”, “physical activity”, “exercise”, “insulin resistance”, “cardiovascular risk”, “obesity”, “lipid profile”, “blood pressure”, and “inflammation. Only peer-reviewed studies published between 2016 and 2025 were included. Eligible articles comprised randomized controlled trials, systematic reviews, and meta-analyses. Additionally, reference lists of selected studies were screened to identify further relevant publications. Results: The data indicate that regular physical activity results in improvements in multiple aspects of MetS. Most included studies and meta-analyses demonstrated approximately 10-17% declines in visceral fat, improved insulin sensitivity (up to 20-25%), reduced triglycerides (approximately 10-15%) and reduced systolic blood pressure (approximately 7 mmHg). Regular physical activity also resulted in decreased levels of inflammatory biomarkers including C-reactive protein. Conclusions: Physical activity should be incorporated into all prevention and management programs for individuals with metabolic syndrome. When prescribing exercise for individuals with metabolic syndrome, consideration should be given to their initial level of fitness, existing comorbid conditions, potential risks and their likelihood of adhering to the program over time.